Imaging in vascular disease. Issue 6 (June 2018) - Horsch, Alexander D.; Weale, Andy R.
Abstract: Accurate imaging and interpretation of the vascular system is fundamental to the management of patients with vascular disease. This is especially important when considering evidence-based intervention for carotid and aneurysmal disease. This article introduces basic principles, advantages and limitations of imaging modalities frequently used to assess patients with vascular disease. The roles of duplex ultrasonography (DUS), computed tomography (CT), magnetic resonance imaging (MRI), and digital subtraction angiography (DSA) in the vascular patient are reviewed.